The impact of transparency on the citizen participation in decision-making at the municipal level in Romania - Radu, Bianca (Central European Public Administration Review, 2019)
The article analyses the implementation of the transparency law and investigates whether its adoption generated more citizens' participation in the decision making process at municipal level in Romania. The research consisted of an analysis of the transparency reports that municipal authorities need to compile every year. We analysed the reports compiled by 28 cities and 5 sectors of the Bucharest municipality for the years 2014, 2015, 2016 and 2017. Additional information about the challenges of the implementation of the law was collected from previous studies conducted by nongovernmental organizations on this topic. The research showed that public institutions increased the transparency of the decision making process by disclosing draft normative proposals and the documents the proposals were based on. The level of citizens' participation in the consultation and deliberation stages of the decision making process remained low over the period analysed, even though a small increase could be observed. The number of recommendations received on draft normative acts was low. The research showed that citizens' suggestions had higher chances to be included in final decisions if they were voiced during Local Council meetings. Besides providing empirical insights in the implementation of the transparency law in Romania, the article provides the researchers with evidence that increased decisional transparency does not automatically lead to greater citizens' involvement in the decision making process.
Keywords: javna uprava; lokalna samouprava; občine; odločanje; participacija; Romunija; transparentnost; udeležba državljanov